Within-Speaker Perception and Production of Two Marginal Contrasts in Illinois English - Zhang, Jennifer; Graham, Lindsey; Barlaz, Marissa; Hualde, José Ignacio (Frontiers in Communication, 2022)
The notion of marginal contrasts and other gradient relations challenges the classification of phones as either contrastive phonemes or allophones of the same phoneme. The existence of “fuzzy” or “intermediate” contrasts has implications for language acquisition and sound change. In this research, we examine production and perception of two marginal contrasts [ɑ-ɔ] (“cot-caught”), where two original phonemes are undergoing a merger and [ʌi-aɪ] (“writer-rider”), where a single original phoneme has arguably split into two contrastive sounds, albeit in a limited manner. Participants born and raised in Illinois were asked to provide recordings of cot-caught and writer-rider pairs embedded in sentences, followed by the target word in isolation. They then completed ABX and two-alternative forced choice (2FC) perception tasks with stimuli produced by two native speakers from the Chicagoland area. Results showed that the [ʌi-aɪ] contrast, which has been defined as marginal in other work, is actually currently more phonetically and phonologically stable than [ɑ-ɔ] for the group of speakers that we have tested, with a more robust link between production and perception. The cot-caught merger appears to have progressed further, compared to what had previously been documented in the region. Our results and analysis suggest different sound change trajectories for phonological mergers, regarding the coupling of production and perception, as compared with phonemic splits.